Creating Identity in the Victorian Fictional Autobiography - Pennington, Heidi L. (Book collections on Project MUSE., 2018)
"This is the first book-length study of the significance of the fictional autobiography in the Victorian understanding of selfhood. Jane Eyre, Villette, David Copperfield, Esther's portions of Bleak House, and other fictional autobiographies of the era subtly but persistently illustrate that all identities are fictions. These works ask readers to rethink the concept of personal identity by showing that our impressions of personal authenticity derive from our own acts of narrative creation. By dramatizing the process of fictional self-making and implicating the reader therein, the fictional autobiography constitutes an important link in the intellectual history of selfhood from pre-Victorian times to the present. In fact, Pennington argues, postmodernism's claims about the constructedness of personal identity represent not a break with traditional thinking about the self, but rather the culmination of it"--